Inspectors' responses to adolescents' assessment of quality of care: a case study on involving adolescents in inspections - Suzanne Rutz; Hester van de Bovenkamp; Simone Buitendijk; Paul Robben; Antoinette de Bont (BMC, 2018)
Abstract Background Users of care services are increasingly participating in inspections of the quality of care. In practice, incorporating service users' views is difficult, as users may have other views on good care than inspectors and thus give information that does not fit the inspectors' assessment criteria. This study compared the views on good care of young care users (adolescents) and inspectors, seeking to understand what the differences and similarities mean to incorporating the users' views in inspections. Methods We conducted a single-case study combining document analysis with a meeting with inspectors. The selected case came from a Dutch inspectorate and involved a thematic inspection of care for children growing up poor. Results Inspectors and adolescents agree on the importance of timely care, creating opportunities for personal development, and a respectful relationship. The views on quality of care differ with regard to sharing information, creating solutions, and the right moment to offer help. We identified three ways inspectors deal with the differences: 1) prioritize their own views, 2) pass the problem onto others to solve, and 3) separate the differing perspectives. With similar viewpoints, inspectors use the adolescents' views to support their assessments. When viewpoints conflict, information from adolescents does not affect the inspectors' judgments. Explanations are related to the vulnerability of the adolescents involved, the inspectorate's organizational rules and routines and the external regulatory context. Conclusions Service user involvement in inspections potentially impacts the quality of care. Yet, conflicts between the views of service users and inspectors are not easily overcome in the regulatory context.